PPV and Frequency Characteristics of Tunnel Blast-Induced Vibrations on Tunnel Surfaces and Tunnel Entrance Slope Faces - Zeming Wang (Hindawi Limited, 2021)
Tunnel blast-induced vibration probably causes damage to the rock mass surrounding the tunnel surface and also to the rock mass of the slope at the tunnel entrance. It is important to simultaneously monitor the vibration on the tunnel surface and on the tunnel entrance slope face, especially when the blasting work face is close to tunnel entrance. During blasting excavation of the traffic tunnel at Baihetan hydropower station, vibration monitors were installed both on the tunnel surface and on the tunnel entrance slope face. Based on the monitoring data, a comparative study is conducted on the peak particle velocity (PPV) and frequency characteristics of the vibrations at these two locations. A three-dimensional FEM simulation of the tunnel blast is then performed to verify the field test results. The field monitoring and the numerical simulation show that there is significant difference between the vibration on the tunnel surface and that on the tunnel entrance slope face. The vibration on the tunnel surface has greater PPV and faster attenuation, while the tunnel entrance slope face has higher frequency and faster reduction rate in the center frequency. These differences are attributed to the different wave types and wave propagation paths. The tunnel surface is mainly surface waves transmitted through the damaged rock mass around the tunnel profile, while the tunnel entrance slope face originates mainly from the body waves transmitted via the undamaged rock mass inside the mountain. The comparisons of the monitored vibrations with the velocity limits specified in the Chinese standard show that the most dangerous vibration that may exceed the limit occurs on the tunnel surface. Therefore, the maximum charge weight used in the tunnel blast is determined by the vibration on the tunnel surface. Under different control standards, the allowable maximum charge weight per delay is further discussed.